Pengaruh Kualitas Layanan Digital, Kepercayaan Nasabah dan Inovasi Produk terhadap Loyalitas Nasabah Bank BNI Cabang KCU Batam - Septiani Indah Wahyuni; Sabri Sabri; Hendri Herman (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to analyze the influence of digital service quality, customer trust, and product innovation on customer loyalty at Bank BNI KCU Batam Branch. A quantitative approach was used by a survey method of 99 respondents selected through a simple random sampling technique from a population of 11,947 customers. The research instrument was in the form of a Likert scale questionnaire, with data analysis using descriptive statistics and multiple linear regression. The results showed that the quality of digital services, customer trust, and product innovation each had a positive and significant effect on customer loyalty, with a t-count value of 10,692; 8,120; and 7.822 (p < 0.05). Simultaneously, the three variables also had a significant effect on customer loyalty with an F-count value of 39.365 (p < 0.05). These findings confirm that improving the quality of digital services, strengthening customer trust, and developing sustainable product innovation are strategic factors in building customer loyalty. This research provides practical implications for banking management to prioritize digital transformation, maintain service integrity, and continue to innovate in products in order to maintain and increase customer engagement. The limitations of this study lie in the scope of location and the number of samples, so the results cannot be widely generalized to all banking branches.